Morphological Responses of Hakonechloa macra (MAk) to Drought and Salinity Stress In vitro - Ismael, Bairam Solomon; Lateef, Sabreen Mohammed; Shukur, Lanja Mohammed; Asker, Saja AL-Layle Qanbar; Parzymiea, Marzena; Kozak, Danuta; Świstowska, Alicja (American Journal of Botany and Bioengineering, 2026)
Using in vitro tissue culture methods, the present work analyses the capacity of the grass species Hakonechloa macra (MAk) to withstand abiotic stresses associated with drought and salinity. The drought stress was simulated through the addition of PEG at various concentrations osmotically (with respect to water) to create different levels of water deficits. The salinity stress was created by adding NaCl to the standard MS medium in order to determine how changes in osmotic pressure affect plant growth. The results show that the morphology of the sample can respond in various ways. There was a significant and negative relationship between the concentration of stress agents (salt) and vegetative growth indicators; tiller number, branch length, and tuft fresh weight. Significant reductions of the root system efficiency were also recorded. Rooting percentages decreased from 76% in the control sample to 0% at high levels of stress agents (1% NaCl), thus indicating that there is extreme sensitivity of the root system to osmotic pressure and ionic toxicity. As a result of this study, there has been a steady increase in the rate of tissue necrosis and a corresponding decrease in the rate of survival of tissues as well, with a total of 30 percent having been reduced from the maximum amount of applied stress experienced. According to this study, Hakonechloa macra has very limited morphological defensive mechanisms that can be used to defend itself from stressful surroundings and therefore should be given very careful consideration with respect to growing in very harsh drought or salt-affected environments.